1985
DOI: 10.1111/j.1471-6402.1985.tb00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Date Rape Justifiable?: The Effects of Dating Activity, Who Initiated, Who Paid, and Men's Attitudes toward Women

Abstract: In two related studies, 268 male undergraduates rated the justifiability of date rape under various circumstances. As predicted, rape was rated as significantly more justifiable (a) if the couple went to the man's apartment rather than to a religious function, (b) if the woman asked the man out rather than vice versa (significant in Study 1 only), and (c) if the man paid all the dating expenses rather than splitting them with the woman. It was also predicted that men who were classified as traditional on the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
2
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(102 citation statements)
references
References 11 publications
4
95
2
1
Order By: Relevance
“…A major difference between female-initiated and male-initiated dates identified in expectations research is that female-initiated dates are expected to involve more sexual activity than male-initiated dates (Mongeau and Carey 1996). Similarly, Muehlenhard et al (1985) also found that participants perceived date rape to be generally unjustifiable on both female-initiated and male-initiated dates, but mean scores for justifiability of date rape were greater for female-initiated than for male-initiated dates. Mongeau and Carey (1996) found the difference in sexual expectations to be greater for men than for women, though data collected along with the data analyzed in this study found no difference in sexual expectations related to gender of the date initiator (see Morr and Mongeau 2004).…”
Section: Gender Of Date Initiatormentioning
confidence: 74%
“…A major difference between female-initiated and male-initiated dates identified in expectations research is that female-initiated dates are expected to involve more sexual activity than male-initiated dates (Mongeau and Carey 1996). Similarly, Muehlenhard et al (1985) also found that participants perceived date rape to be generally unjustifiable on both female-initiated and male-initiated dates, but mean scores for justifiability of date rape were greater for female-initiated than for male-initiated dates. Mongeau and Carey (1996) found the difference in sexual expectations to be greater for men than for women, though data collected along with the data analyzed in this study found no difference in sexual expectations related to gender of the date initiator (see Morr and Mongeau 2004).…”
Section: Gender Of Date Initiatormentioning
confidence: 74%
“…A female-initiated date leads to different sexual expectations than a male-initiated one; specifically, college men expect more sexual activity to occur when the woman initiates the date (Lenton and Bryan 2005;Mongeau and Carey 1996;Mongeau et al 2004;Morr Serewicz and Gale 2008). Although date rape was perceived as unjustifiable regardless of the gender of the date initiator, Muehlenhard et al (1985) found that college students perceived date rape as more justifiable during a female-initiated than a male-initiated date. Thus, men who receive date initiations from women may have expectations of enhanced sexual activity, which may be one of the reasons why women are reluctant to initiate them.…”
Section: Women and Datingmentioning
confidence: 83%
“…Blaming the victim is facilitated by endorsement of rape myths, which are salient not because they are true, but because they are pervasive and believed to be true (Anderson et al, 1997;Barbaree et al, 1991;Holloway & Jefferson, 1998;Janoff-Bullman et al, 1985;Lonsway & Fitzgerald, 1994;Muehlenhard et al, 1985;Simonson & Subich, 1999).…”
Section: Practical Applicationsmentioning
confidence: 96%